The impact of board demographic diversity on firm performance: evidence from China - Yu, Zhuojun (2022)
The board plays a critical role in strategy formulation, oversight and resource provision to improve corporate performance and is influenced by the demographics of directors. The empirical evidence on the relationship between board demographic diversity and firm performance presents inconsistent results. The purpose of this study is to advance research by examining the impact of board demographic diversity on firm performance in the Chinese market. Based on panel data of listed A-share companies in Shanghai and Shenzhen in China from 2010-2019, the study employed a two-factor fixed effects model to conduct separate regression tests on the constructed composite board demographic diversity indicator and the individual demographic attributes comprising it including gender, age, education and tenure. Further testing of the diversity-performance relationship was carried out by dividing the sample into state-owned and private companies according to ownership. The study found that board demographic diversity had an overall positive impact on firm performance. Specifically for the individual variables a linear positive relationship was found between tenure diversity and firm performance, a positive U-shaped curve relation was identified for age diversity, while gender and education were not significantly related. A positive association was found for private firms and a non-significant association for state-owned enterprises under different ownership. The findings complement the evidence from the Chinese context and help to expand the boundaries of the literature in the field of corporate governance and the business case for board demographic diversity research. In addition, this study would contribute to better design of boards and selection of appropriate members by companies, as well as help policy makers to actively develop proposals and laws to guide the composition of boards of directors of Chinese companies in a scientific manner.